Analisa Data Penjualan SaRa Collection menggunakan metode Apriori - Ririn Restu Aria; Susi Susilowati (JURNAL TEKNIK KOMPUTER, 2021)
Sales are one of the most important things in the SaRa collection. To increase the number of existing sales, SaRa collection must be able to see the opportunities and needs needed by its customers. For this reason, when the Covid 19 pandemic is happening now, the SaRa collection has made a connector that can be used to beautify the use of masks to prevent transmission of the Covid 19 virus. In the process of making the connector, it is still done homemade according to the model that consumers are interested in because it takes time to process and select the model. as well as the appropriate color. Currently, sales are still being recorded manually, so the owner is still having trouble providing a stock of the connector model and color that will be made in order to meet consumer demand. In order to find out what models must be provided, accurate calculations are needed, for that the author uses the a priori algorithm as a method which is expected to be taken into consideration in marketing and sales strategies as well as connecting stock data to be made. A priori calculations with itemset and associations based on sales transaction data in Sara's collection